Digital Differentiated Learning: A Web-Based Educational Innovation for Pacitan - Hikmahwan, Bagus; Yuniarti, Dwi Ariani Finda; Putra, Berlian Juliartha Martin; Fu'adi, Anwar; Nugroho, Berto Yusuf (International Journal of Multi Discipline Science (IJ-MDS), 2025)
Technology has the potential to improve the quality and effectiveness of education, especially in remote areas. In Pacitan Regency, East Java, the challenges include limited educational resources and a lack of teaching methods capable of accommodating the diverse needs of students. This gap may impact educational quality, particularly for students with varying levels of understanding and interest. This study aims to design and develop the DGDL (Digital Differentiated Learning) to support differentiated learning in primary and junior high schools in Pacitan. The research employed a development research method, following a systematic approach to designing, developing, and evaluating the DGDL application. The process involved requirement analysis, system design, implementation using PHP, and iterative testing. The development process involved collaboration with the Pacitan Regency Education Office and several local primary and junior high schools. The application was tested through a series of trials involving representative teachers from these schools. Feedback from 17 respondents showed an average score of 4.43 on a scale of 1 to 5, this application was evaluated based on four key aspects: functionality, usability, security, and system performance indicating a high level of appreciation for the application's benefits. This application had proven to be an innovative and relevant solution to address educational challenges in Pacitan, particularly in promoting equitable understanding and enhancing learning quality for all students. Furthermore, future development is expected to adapt the application to various dynamic field conditions and improve its effectiveness in other remote areas.